Combining advantages: Direct correlation of two-dimensional microcomputed tomography datasets onto histomorphometric slides to quantify three-dimensional bone volume in scaffolds - Westhauser, Fabian; Schmidmaier, Gerhard (Journal of biomedical materials research, 2018)
Microcomputed tomography (mCT) belongs to the most powerful tools for the three-dimensional (3D) assessment of bone. While it is possible to refer to landmarks in mCT scans of actual bone structure, the assessment of calcified osteoid within scaffolds is problematic, due to the missing morphological correlates. Therefore, bone formation within scaffolds is mostly analyzed using indirect parameters such as changes in volume or surface alteration, preserving histomorphometry the gold standard in the direct analysis of bone formation. The presented method combines the advantages of mCT and histomorphometry: by creating an overlay image of the exact same histomorphometric and mCT slice, a grey-value-threshold representing calcified tissue was defined. Compared to the scaffolds global threshold, a direct evaluation of bone formation within scaffolds is possible by mCT—applied on the whole dataset, evaluation of bone volume is achievable. Two groups of human mesenchymal-stem-cell-seeded ß-Tricalciumphosphate-scaffolds were analyzed: whilst group B was stimulated with 0.1 µg/mL Bone Morphogenetic Protein-7, group A remained unstimulated during in vivo differentiation. Strong correlations (r > 0.8) were obtained between percentage bone area in mCT and histomorphometry, as well as for 3D bone volume. Using the presented method, 3D bone volume can be directly estimated within scaffolds by combination of histomorphometric and mCT-analysis.